2006
DOI: 10.1345/aph.1h243
|View full text |Cite
|
Sign up to set email alerts
|

A Myoclonic Reaction with Low-Dose Hydromorphone

Abstract: Neuroexcitatory effects of hydromorphone may occur at relatively low doses in patients without renal dysfunction. Early recognition and intervention are required to achieve resolution of these symptoms and prevent further sequelae to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Myoclonus can be triggered or aggravated by a large number of different drugs used in intensive care including opioids, such as hydromorphone (Babul and Darke, 1992;Patel et al, 2006), morphine (Potter et al, 1989), and fentanyl (Stuerenburg et al, 2000); nonsteroidal anti-inflammatory drugs (Bandelot and Mihout, 1978); neuroleptics (Pedavally et al, 2014;Strachan and Benoff, 2006;Vural and Tezer, 2012); antiepileptic drugs in high doses, such as carbamazepine (Magaudda and Di Rosa, 2012), oxcarbazepine (Fanella et al, 2013), lamotrigin (Algahtani et al, 2014), topiramate (Miller et al, 2010), pregabalin and gabapentin (Ege et al, 2008;Healy et al, 2009;Hellwig and Amtage, 2008), phenytoin (Duarte et al, 1996), and valproic acid (Gardner et al, 2009); antidepressants (Caviness and Evidente, 2003;Evidente and Caviness, 1999;Praharaj et al, 2010); the amino acid precursor of dopamine -levodopa (Yoshida et al, 1993) and bromocriptine (Buchman et al, 1987); antibiotics such as imipenem (Frucht and Eidelberg, 1997), cefepime (Fugate et al, 2013), penicillin (Sackellares and Smith, 1979), gentamycin (Sarva and Panichpisal, 2012), ciprofloxacin (Jayathissa et al, 2010), and piperazine (Kompf and Neundorfer, 1974); antihistamines (Irioka et al, 2008); and chemotherapeutics (Denison and Alghzaly, 2006;Savica et al, 2011;Wyllie et al, 1997). Some anesthetics have also been associated with the emergence and aggravation of myoclonus including etomidate …”
Section: Symptomatic Myoclonus In the Icumentioning
confidence: 99%
See 1 more Smart Citation
“…Myoclonus can be triggered or aggravated by a large number of different drugs used in intensive care including opioids, such as hydromorphone (Babul and Darke, 1992;Patel et al, 2006), morphine (Potter et al, 1989), and fentanyl (Stuerenburg et al, 2000); nonsteroidal anti-inflammatory drugs (Bandelot and Mihout, 1978); neuroleptics (Pedavally et al, 2014;Strachan and Benoff, 2006;Vural and Tezer, 2012); antiepileptic drugs in high doses, such as carbamazepine (Magaudda and Di Rosa, 2012), oxcarbazepine (Fanella et al, 2013), lamotrigin (Algahtani et al, 2014), topiramate (Miller et al, 2010), pregabalin and gabapentin (Ege et al, 2008;Healy et al, 2009;Hellwig and Amtage, 2008), phenytoin (Duarte et al, 1996), and valproic acid (Gardner et al, 2009); antidepressants (Caviness and Evidente, 2003;Evidente and Caviness, 1999;Praharaj et al, 2010); the amino acid precursor of dopamine -levodopa (Yoshida et al, 1993) and bromocriptine (Buchman et al, 1987); antibiotics such as imipenem (Frucht and Eidelberg, 1997), cefepime (Fugate et al, 2013), penicillin (Sackellares and Smith, 1979), gentamycin (Sarva and Panichpisal, 2012), ciprofloxacin (Jayathissa et al, 2010), and piperazine (Kompf and Neundorfer, 1974); antihistamines (Irioka et al, 2008); and chemotherapeutics (Denison and Alghzaly, 2006;Savica et al, 2011;Wyllie et al, 1997). Some anesthetics have also been associated with the emergence and aggravation of myoclonus including etomidate …”
Section: Symptomatic Myoclonus In the Icumentioning
confidence: 99%
“…In contrast to epileptic myoclonus, syncope-related myoclonus appears multifocal (Lempert et al, 1994) after the Table 1 The classification of myoclonic movements (based on the work of Fahn et al (Dijk and Tijssen, 2010;Fahn, 2002) Intoxication/drug-related encephalopathy Anesthetic drugs Etomidate (Laughlin and Newberg, 1985;Lumley and Morgan, 1985) Propofol (Tam et al, 2009) Enflurane (Ng, 1980) Opioids Hydromorphone (Babul and Darke, 1992;Patel et al, 2006) Morphine (Potter et al, 1989) Fentanyl (Stuerenburg et al, 2000) Nonsteroidal anti-inflammatory drugs Diclofenac (Bandelot and Mihout, 1978) …”
Section: Potential Misinterpretation Of Non-icu-related Myoclonusmentioning
confidence: 99%
“…2,7-9 Alternatively, a report suggested that doses of 10 mg of intravenous hydromorphone over the course of 2 days in patients without kidney dysfunction led to myoclonic reactions. 17 Our report is distinctive because the patient received much lower doses, suggesting that larger doses are not the only risk factor for the development of neurotoxicity in the presence of kidney dysfunction. It also enhances the growing body of evidence that hydromorphone should be closely monitored in patients with kidney dysfunction.…”
Section: Discussionmentioning
confidence: 71%
“…Patel et al 14 reported the development of myoclonus following a short course of low-dose intravenous opioid treatment. By contrast, no cases of the development of myoclonus following a short course of low-dose oral opioids were identified in this literature search.…”
Section: Opioid-induced Myoclonusmentioning
confidence: 99%